The Effect of Product Diversification and Brand Equity on Purchase Decisions With Promotion Strategy as a Moderator - Oliver Ignatius Tarunay; Yudha Sapta Pratama; Evien (Komunitas Dosen Indonesia, 2024)
Product diversification and brand equity are two critical factors that can influence consumer purchasing decisions. Product diversification can expand the range of products and services available to consumers, while brand equity can create trust and consumer loyalty. Promotion strategies can also serve as a moderator in the relationship between product diversification and brand equity with purchasing decisions. This research aims to analyze the impact of product diversification, brand equity, and promotion strategies on purchasing decisions. This study uses the Structural Equation Modeling (SEM) method with the assistance of Smart PLS software. The Hair method is used to determine the sample size, resulting in 140 respondents. The research results show that product diversification and brand equity have a positive influence on purchasing decisions. Promotion strategies play a moderating role that strengthens the influence of product diversification and brand equity on purchasing decisions, with the coefficient of determination analysis showing a figure of 72.6%, while the remaining 27.4% is influenced by other unexamined factors. Implications for companies indicate that companies aiming to enhance consumer purchasing decisions need to pay attention to two aspects: product diversification and brand equity. Product diversification can be achieved by offering a variety of products that can meet the diverse needs and desires of consumers. Brand equity can be built by creating trust and consumer loyalty. Furthermore, companies also need to use appropriate promotion strategies to enhance consumer purchasing decisions. Promotion strategies can be used to influence consumer perceptions of the products or services offered.